Morphometric and Vascular Analyses and MMP-2 Expression in Bladders of Animals with Bovine Enzootic Haematuria - Archanjo, Anderson Barros; Tamiasso, Natalia Viana; Cosme, Juliana de Castro; Silva, Maria Aparecida da; Trivilin, Leonardo Oliveira; Sequeira, Julio Lopes; Nunes, Louisiane de Carvalho (Acta Scientiae Veterinariae, 2020)
Background: Bovine enzootic haematuria is a chronic, non-infectious disease caused by the ingestion of bracken Pteridium aquilinum that contain ptaquiloside, substance responsible for the development of neoplasms in combination with bovine papillomavirus infection. Studies examining metalloproteinases have shown that these enzymes may be useful as prognostic markers and many studies have correlated the intratumoural microvessel density and incidence of metastasis in a variety of cancers, including bladder cancer. This study aimed to evaluate the urothelial morphology and vasculature and quantify the expression of the enzyme metalloproteinase-2 in the bladder lesions of bovine with enzootic haematuria. Materials, Methods & Results: Forty bladders with macroscopic lesions were subjected to routine histological processing. The material was stained using the Hematoxylin-Eosin (HE) and Weigert's resorcin-fuchsin staining methods. The morphometric analysis included the measurement of the total thickness of the urothelium. Microscopically, the lesions were differentiated as neoplastic or non-neoplastic, and the vascular changes were characterised as vascular proliferation, ectasia, dilation and thickening and the material stained using the Weigert's resorcin-fuchsin method was used to evaluate sclerosis and the vascular fibroelastosis. The metalloproteinase expression was evaluated using an anti-metalloproteinase-2 antibody. The main non-neoplastic lesions found in the urothelium included clear cell metaplasia, dysplasia, hyperplasia, haemorrhage, cystitis cystica and Brunn's nests and the neoplastic lesions were haemangioma, myxoma, transitional cell carcinoma, adenocarcinoma, in situ carcinoma and haemangiosarcoma. The urothelium measurements revealed differences between the epithelial thicknesses of bladders with and without neoplasms. The bladder vasculature evaluation revealed the frequent occurrence of different pathological aspects, such as vascular proliferation, dilation, expansion, ectasia and thickening; more severe vascular proliferation, thickening and fibroelastosis were observed in bladders with neoplasms. Metalloproteinase-2 expression was observed in the epithelial cells, fibroblasts, endothelial cells and smooth muscle cells present in the tumour tissue and was a significant increase in the expression of MMP-2 in the neoplasms of mesenchymal origin compared to the neoplasms of epithelial origin. Discussion: The presence of a large variety of non-neoplastic lesions indicates the possibility that there are other factors concomitant to BEH involved. Epithelial hyperplasia and metaplasia, for example, could be the result of damage caused by bovine papillomavirus type 2 or even an altered urine pH. Furthermore, it is believed that the bladder has the capacity to generate various types of neoplasms due to the different histological components of the bladder, thus enabling it to generate both mesenchymal and epithelial lesions. The thickness of the urothelium was greater in all the quadrants with neoplasms compared to the quadrants without neoplasms. These data revealed that it is possible to use less invasive diagnostic imaging methods to characterise bovine enzootic haematuria and to measure tumour progression based on the severity of vascular changes. The vascular proliferation and thickening were significant in bladders with neoplasms, which may be explained by the fact that tumours require an extensive vascular supply. In addition, many tumours release vascular growth factors and promote neovascularisation. The intensity of the immunostaining of metalloproteinase-2 differed among the different types of neoplasms. However, due to the diversity of the tumours, it was not possible to establish a relationship between metalloproteinase-2 expression and tumour progression.